2020
DOI: 10.3389/fbioe.2020.00392
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of SRC in Extraocular Muscle Fibrosis of the Graves’ Ophthalmopathy

Abstract: The Graves' disease is an autoimmune disease highly associated with thyroid cancer. The Graves' ophthalmopathy (GO) is a special Graves' disease with inflammatory ophthalmopathy being a typical extrathymic complication. GO is caused by the formation of orbital fat and extraocular muscle fibrosis due to the inflammation of orbital connective tissues. Thus, controlling extraocular muscle fibrosis is critical for the prognosis of GO. The objective of this study is to identify and experimentally validate key genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…At first, we cultured primary OFs from GO mice and identified them and then screened the optimal DEX, exosome intervention concentration, and time of OFs. The GO mice used in this project were derived from our recently reported study ( 17 ). It could be seen that the eyes of the mice in the model group are obviously prominent, bulbar conjunctival edema, tears, and increased periocular secretions ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, we cultured primary OFs from GO mice and identified them and then screened the optimal DEX, exosome intervention concentration, and time of OFs. The GO mice used in this project were derived from our recently reported study ( 17 ). It could be seen that the eyes of the mice in the model group are obviously prominent, bulbar conjunctival edema, tears, and increased periocular secretions ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The GO animal model was established by Balb/c female mice aged 8–10 weeks. The establishment method of the model group was the same as our previous study ( 17 ), and the control group was given the same amount of PDF. After modeling, 3 mice in the model group and control group were randomly sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…SRC belongs to the non-receptor protein-tyrosine kinases family, playing key roles in cell growth, division, migration, and survival signaling pathways [ 41 ]. Multiple studies indicated that SRC regulated the PI3K-AKT pathway in inflammation-related diseases such as multiple sclerosis (MS), Grave’s Disease (GD), and in the neutrophil extracellular traps (NET) formation [ 42 , 43 , 44 ]. In our experiments, we found that the phosphorylation level of SRC was significantly upregulated in hepatic tissue in two AIH models and was drastically decreased in the costunolide group.…”
Section: Discussionmentioning
confidence: 99%
“…While peroxisome proliferator-activated receptor-c (PPAR-c) signal transduction has been identified as the primary inducer of adipogenesis [31,32], studies have revealed interactions between TGF-β signaling and PPAR-c signaling [33]. Studies have shown that the Smad signal plays an important role in periorbital fibrosis in TAO [34][35][36], and Smad7 is predicted to be one of the target genes of miR-96-5p (StarBase, URL: http://starbase.sysu.edu.cn/agoClipRNA. php?source�mRNA).…”
Section: Introductionmentioning
confidence: 99%